"Old and Dirty Gods": Religion and Freud's Wednesday Night Psychological Society—from Habsburg Vienna, to the Holocaust. Issue 1 (2nd January 2017) - Cooper-White, Pamela
Abstract : Freud's insistent atheism—and his somewhat contradictory, obsessional return to the topic of religion throughout his cultural writings—are both well documented. In a 1918 letter to the Swiss pastor-psychoanalyst Oskar Pfister, he described himself as "a completely godless Jew." Less well known, however, are the attitudes toward religion among Freud's "Wednesday Night Psychological Society"—Freud's immediate circle of psychoanalysts in Vienna, Austria. Historian Peter Gay in his critical biography of Freud concluded that "Freud's view of religion as the enemy was wholly shared by the first generation of psychoanalysts. The attempts of some later psychoanalysts to reconcile psychoanalysis with religion would never have found the slightest sympathy in Freud and his colleagues." This article will contest this premise based on my research as a Fulbright Fellow at the Sigmund Freud Museum in Vienna in 2013-14, beginning with the research question: "What religious themes appear in discussions and writings of Freud's Wednesday Night Psychological Society?" Sources include the recorded Minutes of the group and its cultural journal Imago, through the vicissitudes, conflicts and expansions of the Society from its founding in 1902 to the year of its dissolution in the face of the Nazi terror of 1938 in Austria—and the ways in which their views on religion were more complex than traditionally assumed. In addition, this research uncovered the crucial impact of antisemitism as total context on the origins of psychoanalysis, fuelled by the close relationship between Catholicism and the Austrian Habsburg regime. The first analysts' attitudes toward religion cannot be fully understood without taking this context of oppression into consideration. The article concludes with implications for the discipline of pastoral theology and pastoral psychotherapy.